Studi Genealogis atas Tradisi Tumbilatohe di Gorontalo: Sebuah Analisis Foucauldian - Busura, Mohamad Rifaldi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The Tumbilatohe tradition, the practice of lighting lamps ahead of Eid al-Fitr, is mainstreamly narrated as an